The Effect of Brain Game on Cognitive Function in Stroke Patients - Novi Malisa; Yuke Kirana (Faculty of Nursing Universitas Padjadjaran, 2021)
The decline in cognitive function has been a disorder frequently experienced by stroke patients. The present study aimed to determine the effect of android-based brain games on cognitive function in stroke patients. Brain games in this study are designed using an exploratory approach to various cognitive function domains that are damaged. The quasi experiment using two groups pretest and posttest design involved 15 individuals for each group recruited from a hospital in West Java through purposive sampling with a sample calculation formula using a paired numerical analytical research formula. The intervention group received an android-based brain games three times a week for one month, the control group received placebo intervention (mentioning colors of different words) three times a week for one month. The FACT-Cog Version 3 questionnaire utilized as the measuring instrument. Measurements were taken every week after the intervention for one month. The results indicated that there was a significant change in cognitive function scores before and after the intervention in the intervention group (p = 0.000). Meanwhile, in the control group there is no significant change (p = 0.164). Moreover, the results of cognitive function score analysis after intervention between the intervention and control group exhibit a significant difference (p = 0.000). The brain game intervention has a significant effect on cognitive function after the third treatment in the first week (p <0.05). Also, the results exhibit the potential effect of brain games on the cognitive function level of stroke patients. Some of the things that make the intervention in this study effective in improving cognitive function are that the respondents included in this study are only those who have a score greater than or equal to 46, which may be different when applied to patients with lower scores. In addition, the intervention was carried out on respondents who had experienced a stroke for the first time and may be different if applied to people who have had several strokes. Therefore, it is important to expand the criteria for respondents in further research. Furthermore, this can be used as an option of the nursing intervention to manage cognitive problems among stroke patients.